2012
DOI: 10.1177/193229681200600407
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Local Blood Flow by Warming the Application Site: Beneficial Effects on Postprandial Glycemic Excursions

Abstract: The absorption profile of rapid-acting insulin analogs delivered subcutaneously is slow compared with physiological insulin. Shorter time to peak and shorter duration of insulin action are important steps toward reducing high postprandial blood glucose concentrations in diabetes therapy and are critical for the development of a closed-loop insulin delivery system. Many attempts have been made to develop more rapid-acting insulins. Since the 1950s, different approaches, such as jet injectors and sprinkler needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…Without comparable (i.e., identical) glucose/insulin levels in the last hour(s) prior to the intervention (i.e., ingestion of the meal/insulin application), the validity of comparing the results obtained on different study days is compromised. With the UFIs presented here, some meal-related studies fulfilling these requirements have been performed demonstrating their benefits also in comparison with RAIAs (see the other related manuscripts 18,25,30,48,49,54 ). One can envisage head-to-head comparisons involving two or more of the approaches presented in a given study under identical UFI conditions that would allow one to make clear statements about the pros and cons of the studied developments.…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Without comparable (i.e., identical) glucose/insulin levels in the last hour(s) prior to the intervention (i.e., ingestion of the meal/insulin application), the validity of comparing the results obtained on different study days is compromised. With the UFIs presented here, some meal-related studies fulfilling these requirements have been performed demonstrating their benefits also in comparison with RAIAs (see the other related manuscripts 18,25,30,48,49,54 ). One can envisage head-to-head comparisons involving two or more of the approaches presented in a given study under identical UFI conditions that would allow one to make clear statements about the pros and cons of the studied developments.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The Israel-based company InsuLine (see the article by Freckmann and associates 18 in this special theme issue) has developed small patch devices to apply mild heat (38 °C) locally to the skin at the time of a SC insulin injection or bolus from an insulin pump.…”
Section: Increase Of Local Blood Flowmentioning
confidence: 99%
“…Prowadzono badania kliniczne z urządzeniem InsuPatch ogrzewającym miejsce iniekcji i zwiększającym ukrwienie, co przyczyniało się do szybszego wchłaniania insuliny. Urządzenie to w domyśle mogłoby zostać zintegrowane z pompą insulinową i poprawić jej działanie [6][7][8].…”
Section: Ultraszybkodziałające Analogi Insulinunclassified
“…Clinical trials have been conducted with an InsuPatch device heating the injection site and increasing blood supply, which resulted in more rapid insulin absorption. This device might be integrated with an insulin pump thus improving the functioning of the pump [6][7][8].…”
Section: Rapid-acting Insulinmentioning
confidence: 99%
“…Recent studies with this device have shown that infusion site warming in patients with type 1 diabetes increased local blood flow and reduced postprandial glycemic excursions. [7][8][9] Using the glucose clamp technique, improvements in the pharmacokinetics (PK) and pharmacodynamics (PD) of a standard bolus dose of aspart insulin were observed with infusion site warming in young, pumptreated patients with type 1 diabetes. 10 The InsuPad is an alternative skin-warming device that was designed for patients receiving basal-bolus multiple daily injection therapy.…”
mentioning
confidence: 99%